If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6f + 14g) = 0 (6f * 4 + 14g * 4) = 0 (24f + 56g) = 0 Solving 24f + 56g = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-56g' to each side of the equation. 24f + 56g + -56g = 0 + -56g Combine like terms: 56g + -56g = 0 24f + 0 = 0 + -56g 24f = 0 + -56g Remove the zero: 24f = -56g Divide each side by '24'. f = -2.333333333g Simplifying f = -2.333333333g
| 12s-/5=6 | | 3x-4+5x=0 | | 8x(1/9) | | 4(4x)+4(5y)=4(4x+5y) | | -5(1.4)x=-5927 | | 1.53=x^2 | | 4(6x+14g)= | | x^2+3x=7x+34 | | -7(n-4)=56 | | 5-x/8=2 | | -4+7s+3-2s= | | 0.12x=140 | | 7(3a+4y)= | | 3c+12=5c+11.04 | | 3(6x+10y)= | | -(n-6)=27+2n | | 43/4x5= | | y+4y-20=180 | | 3+5=40 | | 9/-15=27/p | | y+4y-20=189 | | 2(2d+3e)= | | -30=5/3(41.6) | | cos(2x)+7cos(x)+4=0 | | 16lnx=24 | | 8v=2(40+2) | | 61=1 | | f(x)=30+0.2(5) | | 2b+6(2-6)=-b | | 2(4x)+2(5x+18)=360 | | 4x-x-24=0 | | -9(6+g)-2g=-10 |